Combination of Systemic Chemotherapy with Local Stem Cell Delivered S‐TRAIL in Resected Brain Tumors. (January 2015) - Redjal, Navid; Zhu, Yanni; Shah, Khalid
Abstract Despite advances in standard therapies, the survival of glioblastoma multiforme (GBM) patients has not improved. Limitations to successful translation of new therapies include poor delivery of systemic therapies and use of simplified preclinical models which fail to reflect the clinical complexity of GBMs. Tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) induces apoptosis specifically in tumor cells and we have tested its efficacy by on‐site delivery via engineered stem cells (SC) in mouse models of GBM that mimic the clinical scenario of tumor aggressiveness and resection. However, about half of tumor lines are resistant to TRAIL and overcoming TRAIL‐resistance in GBM by combining therapeutic agents that are currently in clinical trials with SC‐TRAIL and understanding the molecular dynamics of these combination therapies are critical to the broad use of TRAIL as a therapeutic agent in clinics. In this study, we screened clinically relevant chemotherapeutic agents for their ability to sensitize resistant GBM cell lines to TRAIL induced apoptosis. We show that low dose cisplatin increases surface receptor expression of death receptor 4/5 post G2 cycle arrest and sensitizes GBM cells to TRAIL induced apoptosis. In vivo, using an intracranial resection model of resistant primary human‐derived GBM and real‐time optical imaging, we show that a low dose of cisplatin in combination with synthetic extracellular matrix encapsulated SC‐TRAIL significantly decreases tumor regrowth and increases survival in mice bearing GBM. This study has the potential to help expedite effective translation of local stem cell‐based delivery of TRAIL into the clinical setting to target a broad spectrum of GBMs. Stem Cells2015;33:101–110